2012
DOI: 10.3390/ijerph9082562
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and Spatial and Temporal Variations of Disinfection By-Products in the Water and Air of Two Indoor Swimming Pools

Abstract: In order to improve disinfection by-product (DBP) exposure assessment, this study was designed to document both water and air levels of these chemical contaminants in two indoor swimming pools and to analyze their within-day and day-to-day variations in both of them. Intensive sampling was carried out during two one-week campaigns to measure trihalomethanes (THMs) and chloramines (CAMs) in water and air, and haloacetic acids (HAAs) in water several times daily. Water samples were systematically collected at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
25
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(27 citation statements)
references
References 62 publications
(95 reference statements)
1
25
0
1
Order By: Relevance
“…Moreover, some studies have indicated that exposure to THMs can have effects on reproductive health, such as intrauterine growth retardation, low birthweight, preterm birth, congenital malfunctions, stillbirth, and small for gestational age (SGA) neonates (Bove et al., ; Graves et al., ; Huang and Jaakkola, ; Levallois et al., ; Nieuwenhuijsen et al., ). Although most of the aforementioned studies on the effects of exposure to THMs on health analyzed household water use activities (e.g., consumption or showering) instead of analyzing the effects of swimming pool attendance (Catto et al., ), the potential health risks related to chemical exposures in swimming pools is still a public health concern.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Moreover, some studies have indicated that exposure to THMs can have effects on reproductive health, such as intrauterine growth retardation, low birthweight, preterm birth, congenital malfunctions, stillbirth, and small for gestational age (SGA) neonates (Bove et al., ; Graves et al., ; Huang and Jaakkola, ; Levallois et al., ; Nieuwenhuijsen et al., ). Although most of the aforementioned studies on the effects of exposure to THMs on health analyzed household water use activities (e.g., consumption or showering) instead of analyzing the effects of swimming pool attendance (Catto et al., ), the potential health risks related to chemical exposures in swimming pools is still a public health concern.…”
Section: Introductionmentioning
confidence: 99%
“…Catto et al. () suggested that the contribution of each exposure route depends on the environmental concentrations and on the ratio between air and water levels.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations